Local injection of adipose-derived mesenchymal stem cells in silk fibroin solution on the regeneration of lower esophageal sphincter in an animal model of GERD - Zhang, Daxu; Wang, Zhanbo; Ma, Lianjun; Xu, Lijuan; Fan, Suna; Su, Yinan; Shi, Xiaonan; Hu, Jingjing; Zhao, Shuo; Li, WeiLong; Linghu, Enqiang; Yan, Li (Frontiers in Cell and Developmental Biology, 2023)
A few of tissue engineering techniques utilizing adult stem cells and biomaterials are currently being explored to regenerate vessel, cardiac muscle, bladder and intestine. However, there were few reports on the regeneration of Lower Esophageal Sphincter (LES), which was associated with the Gastroesophageal Reflux Disease (GERD). This study aimed to determine whether Adipose-Derived Stem Cells (ADSCs) combined with regenerated silk fibroin (RSF) solution could regenerate the LES. In vitro, the ADSCs were isolated, identified and then were cultured with an established smooth muscular induction system. In vivo, in the experimental groups, CM-Dil labeled ADSCs or induced ADSCs mixed with RSF solution were injected into the LES of rats after the establishment of animal model of GERD respectively. Results showed that ADSCs could be induced into smooth muscular-like cells with the expression of calponin, haldesmon, a-smooth muscle actin and smooth muscle-myosin heavy chain in vitro. In vivo, the thickness of LES of the experiment rats were much thicker than those in the controlled groups. This result indicated that ADSCs mixed with RSF solution might contribute to the regeneration of the LES, thus reduce the occurrence of the GERD.